Efficacy of Platelet-Rich Fibrin in Alveolar Ridge Preservation Following Minimally Traumatic Tooth Extraction - Weng, Yun (Archive of Orofacial Data Science, 2024)
AIM: The application of platelet-rich fibrin (PRF) in alveolar ridge preservation (ARP) has been shown to enhance treatment outcomes. The aim of this study is to systematically review the efficacy of PRF in the preservation of alveolar ridge following minimally traumatic tooth extraction. METHODS: A comprehensive literature search was conducted with the publication date set to the past 10 years. A total of 26 controlled clinical trials met the inclu- sion criteria and were included for review. The outcome parameters analysed included post-operational morbidity, soft tissue healing, changes of alveolar dimension, and bone formation in the socket. RESULTS: All included studies treated the test sites with PRF, and the control sites were left for spontaneous healing. The tooth extraction procedures were kept min- imally traumatic. A pronounced post-extraction pain reduction effect was reported in the test sites, with corresponding fewer analgesic consumptions. PRF-treated sites demonstrated accelerated soft tissue healing. The applied PRF reduced bone atrophy and led to an appreciable quantity of new bone formation in the socket, thereby sus- taining the bone volume. CONCLUSION: PRF ameliorates immediate post-operational discomfort, improves soft tissue healing, and enhances bone tissue preservation and regeneration. Clini- cal application of PRF is effective and should be considered as a biomaterial for ARP following dental extractions.